Diagnosis of Baby Blues Syndrome sing the Certainty Factor Method (Case Study: FULL BETHESDA Hospital) - Sulisni; Fauzi, Achmad; Ramadani, Suci (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2023)
Baby blues syndrome is a psychological disorder experienced by women after giving birth, such as feeling excessively upset and sad, and tired for no apparent reason. About 80% of women who have just given birth will experience Baby blues Syndrome, if this continues and is prolonged it will be very dangerous for the health of the mother and baby. From the problems above, the hospital needs to have an additional system that can help make it easier for the medical team to speed up handlers in analyzing and diagnosing Baby blues Syndrome suffered by patients using the certainty factor method. The purpose of this research is to build an expert system for diagnosing the symptoms of Baby blues syndrome using the certainty factor method. Based on the results of the CF calculation, the highest score is the type of baby blues syndrome with a value of 0.9602 or 96.02%. From the results obtained, the system identified that the patient had a type of baby blues syndrome.